Современные возможности профилактики и терапии сосудистых когнитивных нарушений - А. А. Фирсов; А. А. Смирнов; Т. А. Усанова; С. В. Фирсова (SINAPS LLC, 2013)
This discussion article presents necessary information for general practitioners and neurologists concerning vascular brain disorders and post-insult conditions. Also authors discuss aspects of the epidemiology, risk factors, pathogenesis and treatment of stroke, particularly in conservative therapy of stroke, neuroprotective agent of the citicoline (Ceraxon). Case from neurologist practice is shown.